Insights into the nutritional value of honeybee drone larvae (Apis mellifera) through proteomic profiling - Eliza Matuszewska-Mach; Kacper Packi; Natalia Rzetecka; Wojciech Wieliński; Zenon J. Kokot; Dariusz Kowalczyk; Jan Matysiak (Scientific Reports)
Abstract There is a growing interest and demand for insect-based foods. Edible insects are rich in protein and other nutrients, making them valuable in the daily diet. However, their composition is not yet fully characterised. Therefore, this study aimed to analyse for the first time the qualitative proteome of honeybee (Apis mellifera) drone larvae using sophisticated sample preparation techniques and mass spectrometry. A total of 109 proteins were identified in the larvae. Of these, the largest plurality (38%) were enzymes. In addition, we identified proteins considered to be allergens - the cause of potentially dangerous effects after insect consumption. The results of the analyses may suggest that honeybee larvae are a protein-rich product, with over 100 unique proteins identified based on 1080 peptides. Enzymes indicate intensive development of the larvae. However, as well as nutritious compounds, honeybee larvae contain dangerous allergens. The composition of bee larvae needs to be further tested to make them safe for consumption.